No longer children: what do Young Lives children do when they grow up? Transitions to post-secondary education and the labour market - Favara, Marta (2018)
No longer children: What do Young Lives children do when they grow up? is a Young Lives research report, synthesising research from the past two survey rounds (in 2013 and 2016) to reflect on how the experience of poverty early in life affects future opportunities, documenting children and young people’s trajectories from school into post-secondary education and the labour market, and investigating their chances to access productive jobs.